Colección Fundación Arco 1987/1992. - Centro Cultural Conde Duque, Madrid (Madrid : IFEMA - Institucion Ferial de Madrid, 1993)
Andre, Carl ; Clemente, Francesco ; Kounellis, Jannis ; Polke, Sigmar ; Rainer, Arnulf ; Salvo ; Solano, Susana ; Appel, Karel ; Buren, Daniel ; Long, Richard ; Serra, Richard ; Turrell, James ; Charlton, Alan ; Judd, Donald ; Knoebel, Imi ; Rückriem, Ulrich ; Bishop, James ; Darboven, Hanne ; Forns Bada, Carlos ; Kapoor, Anish ; LeWitt, Sol ; Merz, Mario ; tuttle, Richard ; Veneman, Peer ; Alberola, Jean Michel ; Boltanski, Christian ; Flavin, Dan ; Horn, Roni ; Lucebert ; McCollum, Allan ; Blais, Jean Charles ; Christo ; Lucebert ; Mangold, Robert ; Scully, Sean ; Shapiro, Joel ; Soto, Jesus
Colección Fundación Arco 1987/1992, Centro Cultural Conde Duque, Madrid, 9 febrero / 11 abril 1993
boek